Effect of Self-Monitoring on Personal Hygiene Among Individuals With Developmental Disabilities Attending Postsecondary Education. (November 2019) - Gushanas, Christina M.; Thompson, Julie L.
Research indicates that employers rate personal hygiene as the number one barrier to employment among individuals with developmental disabilities. However, there is limited literature on improving personal hygiene in preparation for employment among individuals with developmental disabilities. Using a multiple-baseline across-participants design, this study examined the effect of self-monitoring on personal hygiene among five individuals with developmental disabilities, ages 19 to 22 years, attending a postsecondary education program. A functional relation was demonstrated between self-monitoring and reduced distracting body odor. Limitations, suggestions for future research, and practical applications are provided.